Eigenvalue Analysis and Simultaneous Nilpotence in Intuitionistic Fuzzy Matrices (European Journal of Pure and Applied Mathematics, 2025)
Nilpotent intuitionistic fuzzy matrices are an important tool for analysis of intuitionistic fuzzy matrices. We first examine different nilpotent conditions of such matrices in terms of their eigenvalues in this research work. The notion of nilpotence is generalized to propose simultaneous nilpotence for a finite set of intuitionistic fuzzy matrices. Simultaneous nilpotence is the situation in which an infinite product of a finite number of intuitionistic fuzzy matrices approaches the zero matrix. The basic properties of this extended concept are also formulated.
Keywords: EigenValues, Simultaneous Nilpotence , Directed Graph